THE ISSUE OF PROFESSIONAL SELF-AWARENESS IN THE SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF HIGHER EDUCATION STUDENTS - Yadgarova, Ozoda Ibragimovna (SCIENCE and SOCIETY, 2026)
The article analyzes the socio-psychological characteristics of higher education students, specifically the formation of professional identity among future foreign language specialists. The study highlights the attitudes of philology students toward psychological knowledge and their professional motivation based on empirical data. Practical recommendations for developing a professional “Self-concept” among students have been formulated based on the results.